2011
DOI: 10.1016/j.breast.2010.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and prognostic markers in breast cancer

Abstract: We have found that lobular cancer (and thereby also diploid tumours) are connected, independently, to age at first childbirth and possibly also to number of children but no other correlations between reproductive data, breastfeeding included, and prognostic markers used in this study were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…This is given support by recent research showing that the more hormones a woman consumed the more aggressive was the breast cancer developed, which may be explained by the fact that estradiol stimulate angiogenesis (Stoner et al, 2004;Seeger et al, 2006;Loof-Johanson et al, 2011;Caliceti et al, 2013).…”
Section: Discussionmentioning
confidence: 60%
“…This is given support by recent research showing that the more hormones a woman consumed the more aggressive was the breast cancer developed, which may be explained by the fact that estradiol stimulate angiogenesis (Stoner et al, 2004;Seeger et al, 2006;Loof-Johanson et al, 2011;Caliceti et al, 2013).…”
Section: Discussionmentioning
confidence: 60%
“…Several studies have been done to explain the association of breastfeeding and parity with breast cancer [4,[24][25][26][27][28][29][30][31][32][33][34][35][36]. For instance, Dall et al [33] found that parity in younger pregnancies decreases breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic markers and tumor properties of prognostic significance for breast cancer and reproductive data, including breastfeeding history, have been previously presented 16,18 and are merely summarized here. The Nottingham prognostic index (NPI) is a weighted sum of the following three parameters: 0.2 · tumor size (cm) + LNS (lymph node status having the value 1 with no nodes affected, 2 with 2-3 nodes affected, and 3 with >3 affected) + the Nottingham histological grade (NHG) (assessed as 1, 2, or 3).…”
Section: Prognostic Markers Reproductive and Breastfeeding Datamentioning
confidence: 99%
“…At the beginning of this study, 275 out of 629 women had died (44%), and 10 women in terminal care were excluded (1.6%). During 2004, all living women (n = 345) were sent a questionnaire regarding breastfeeding and reproduction-related variables, including number of children, time of their children's births, and duration of breastfeeding 16 ; 250 out of 345 women responded (72%).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation